Research Progress on the Pathogenesis and Traditional Chinese Medicine Treatment of Cervical Spondylotic Radiculopathy - Yang, Shudi; Qiao, Haifa (Journal of Contemporary Medical Practice, 2026)
Cervical spondylotic radiculopathy is one of the common clinical types of cervical spondylosis. Its main clinical manifestations include radiating pain, numbness, and weakness in the neck, shoulders, and upper limbs, which exert a considerable impact on people’s daily life and work. The pathogenesis and etiology of this disease remain unclear and are generally considered to be the result of the combined action of multiple factors. Its incidence has been increasing year by year, and the affected population is becoming younger. Conservative treatment remains the main therapeutic approach. Traditional Chinese medicine is convenient, effective, and highly safe in the treatment of cervical spondylotic radiculopathy, and its clinical application has become increasingly widespread. In this paper, relevant literature on the treatment of cervical spondylotic radiculopathy with traditional Chinese medicine over the past 10 years was collected and reviewed, and the potential mechanisms and current research status of traditional Chinese medicine treatment for cervical spondylotic radiculopathy were summarized for reference.